Drawing a line of demarcation. Issue 198 (1st December 2019) - Pfaller, Robert
AbstractThe text is a rewritten lecture on the staging of Mateja Bučar's dance installation On(the)line performed in Cankarjev dom on 6 October 2017. The author writes about Althusser's demarcation line between ideas deemed to be right and ideas deemed to be wrong. He makes a connection with Freud's call to differentiate between science and theoretical ideology, which itself says that it has always claimed the same thing. In this sense, not even the enemy is simply the absolute other, but rather an alter ego.